2022
DOI: 10.1007/s00421-022-05106-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute heat exposure on the determination of exercise thresholds from ramp and step incremental exercise

Abstract: The aim of this study was to examine how respiratory (RT) and lactate thresholds (LT) are affected by acute heat exposure in the two most commonly used incremental exercise test protocols (RAMP and STEP) for functional evaluation of aerobic fitness, exercise prescription and monitoring training intensities. Eleven physically active male participants performed four incremental exercise tests, two RAMP (30 W•min -1 ) and two STEP (40 W•3 min -1 ), both in 18°C (TEMP) and 36°C (HOT) with 40 % relative humidity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In our study, a 6.5 ± 3.3% decrease in PO at CP was found in HOT compared with TEMP, which was similar in women and men. This is consistent with the majority of the studies that showed a reduction in the absolute PO corresponding to the maximal metabolic steady state with acute heat exposure (Bourgois et al, 2023; de Barros et al, 2011; Lorenzo et al, 2011; Maunder et al, 2021). It has been noticed that the extent of the reduction, induced by heat, varies between studies, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, a 6.5 ± 3.3% decrease in PO at CP was found in HOT compared with TEMP, which was similar in women and men. This is consistent with the majority of the studies that showed a reduction in the absolute PO corresponding to the maximal metabolic steady state with acute heat exposure (Bourgois et al, 2023; de Barros et al, 2011; Lorenzo et al, 2011; Maunder et al, 2021). It has been noticed that the extent of the reduction, induced by heat, varies between studies, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…PO corresponding to the maximal metabolic steady state with acute heat exposure (Bourgois et al, 2023;de Barros et al, 2011;Lorenzo et al, 2011;Maunder et al, 2021). It has been noticed that the extent of the reduction, induced by heat, varies between studies, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation